Use of "natural" oils for moisturization: Review of olive, coconut, and sunflower seed oil. Issue 1 (28th August 2018) - Karagounis, Theodora K.; Gittler, Julia K.; Rotemberg, Veronica; Morel, Kimberly D.
Abstract: Despite the availability of effective medications for the management of atopic dermatitis and xerosis, patients may use nonconventional therapies such as topical oils. Patients choose these treatments because of the perceived lower risk of natural products and the fear of potential adverse effects of topical steroids. We review the use of topical olive, coconut, and sunflower seed oil in the treatment of atopic dermatitis and xerosis with a focus on children Currently available evidence suggests that olive oil may exacerbate xerosis and atopic dermatitis. Further studies are needed to make definitive recommendations regarding the use of coconut and sunflower seed oil.